The Collective Model of the Household and an Unexpected Implication for Child Labor: Hypothesis and an Empirical Test - Basu, Kaushik; Ray, Ranjan (World Bank, Washington, D.C., 2013)
The authors use the collective model of the household and show, theoretically, that as the woman's power rises, child labor will initially fall, but beyond a point it will tend to rise again. A household with a balanced power structure between the husband and the wife is least likely to send its children to work. An empirical test of this relationship using data from Nepal strongly corroborates the theoretical hypothesis.